RUKUN KEMATIAN: KEARIFAN LOKAL DAN MODAL SOSIAL BAGI KERUKUNAN UMAT BERAGAMA DI KOTA BANDAR LAMPUNG - Haidlor Ali Ahmad (Harmoni, 2015)
This study investigates two funeral organizations (rukem) in Bandar Lampung. Those are Rukem Village III Surabaya and Rukem Block L Village Bukit Permai Kemiling. The purposes of this study are: 1). Identifying funeral organization as local culture and social capital to interreligious harmony; 2). Uncovering the activities of funeral organization in order to maintain the harmonious life; 3). Revealing the factors that can support and hinder the harmony. The results show: firstly, the establishment of funeral organization is based on fardlu kifayah in dealing with the body and eases the burden on residents who are suffering and grieving. Secondly, funeral organization is local culture and social fund bonding all muslims and bridging interreligious group. Thirdly, Bandar Lampung city has conducive condition that supports to mantain the religious harmony. Moreover, it is found a visiting tradition among the religious groups both in joyful and sorrowful condition. The inhibiting factors are lack of citizen awareness to the benefit of funeral organization and local government (Pemkot) and central government (ministry of religious affairs) have less attention to the funeral organization. It can be revitalized in order to maximize its role in maintaining the internal islamic harmony and interreligious group if the local government concern to the funeral organization.